EFEKTIVITAS PEMBELAJARAN MATEMATIKA SECARA DARING DITINJAU DARI SELF-DETERMINATION - Rafiq Zulkarnaen (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
Online mathematics learning is able to facilitate curriculum demands in the Covid-19 pandemic, but the impact on student motivation is always ignored. This study aims to examine the relationship between student self-determination in the teacher's perspective and teacher self-determination towards online learning, either partially or simultaneously. A descriptive-correlational survey design was used in this study, with five mathematics teachers in Junior High Schools in Bandung as subjects, which were taken by convenience sampling. Questionnaires and unstructured interviews were used in this study. The questionnaire used to collect self-determination data was adopted from The American Institutes for Research Self Determination Questionnaire, while the online learning quality questionnaire was adopted from Alarcón et al. (2020). The results showed that there was a positive relationship: between student self-determination in the teacher's perspective and teacher self-determination towards online learning either partially or simultaneously, between aspects of teacher capacity in self-determination on teacher's digital-pedagogical abilities and digital resources, between aspects of student capacity in the teacher's perspective on student empowerment and student digital competence, between student capacity and teacher capacity for the implementation of online learning. Furthermore, the perception of mathematics teachers towards online learning are key elements in the effectiveness of online mathematics learning.